The Poverty of Privacy? - McClain, Linda C. (Columbia Journal of Gender and Law, 1992)
This Article has two aims. First, it defends a continuing role for the right of privacy in arguments -for women’s reproductive freedom against charges that privacy is an impoverished concept. Second, it raises cautions about certain feminist critiques of privacy that would ground this freedom in notions of reproductive responsibilities. As this Article was first pre- sented at a conference, “Reproductive Issues in a Post-Roe World,” held in the wake of Webster v. Reproductive Health Services, the first question is: Are we now, given the Supreme Court’s recent decision in Planned Parenthood v. Casey, in a “post-Roe world”? Furthermore, what remains of the right of privacy?